EFFECT ON PERFORMANCE LEADERSHIP TRAINING AND HOSPITAL NURSE ON MOTHER CHILD HOSPITAL ERIA BUNDA PEKANBARU - Melan Andriani; Marzolina '; Restu Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study performed on mother child hospital Eria Bunda Pekanbaru. This study destination to determine how the variables influence and leadership training simultaneously and partially on the performance of nurses on mother child hospital Eria Bunda Pekanbaru. As for the population in the study was the nurses who work on mother child hospital Eria Bunda Pekanbaru which amounts to 69 people. Analysis of the data used is descriptive analysis, as it also uses namely Quantitative Analysis using multiple linear regression with the help of SPSS (Statistical Package for Social Science) version 17.0. From the results of the testing that has been done, simultaneous regression test or F test showed that the training and leadership have a significant effect on the performance of nurses. The results of the partial test or T test showed that the training variables partially significant effect on the performance of nurses. And leadership variables partially significant effect on performance. Of the independent variable is known that training has a dominant influence on the performance.Keywords: performance, training and leadership